Versican and Tumor-Associated Macrophages Promotes Tumor Progression and Metastasis in Canine and Murine Models of Breast Carcinoma - dos Reis, Diego Carlos; Damasceno, Karine Araújo; de Campos, Cecília Bonolo; Veloso, Emerson Soares; Pêgas, Gabriela Rafaela Arantes; Kraemer, Lucas Rocha; Rodrigues, Michele Angela; Mattos, Matheus Silvério; Gomes, Dawidson Assis; Campos, Paula Peixoto; Ferreira, Enio; Russo, Remo Castro; et al. (Frontiers in Oncology, 2019)
Versican and tumor-associated macrophages (TAMs) are involved in growth and metastases in several cancers. Here, we investigated the potential role of versican, a matrix proteoglycan, and its correlation with TAMs infiltrates in different stages of two different breast cancer models: spontaneous canine mammary gland carcinomas and the murine 4T1 breast cancer model. The stromal versican expression was correlated with TAMs accumulation in tumors with an advanced stage from spontaneous canine mammary carcinoma samples. Versican expression in mice, identified in late stages of tumor progression, was associated to a high number of peri-tumoral infiltrating TAMs. Indeed, TAMs were related to a pro-inflammatory and pro-angiogenic state in the primary tumor. Furthermore, TAMs accumulation was related to versican expression in the lungs and an increased number of pulmonary metastatic nodules with pulmonary mechanical dysfunction, which was due to leukocyte influx in the airways and elevated growth factor levels in the microenvironment. Thus, we suggest that versican and TAMs as attractive targets for breast cancer therapy.